(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Background: Leukotriene receptor antagonists have been studied in the management of moderate to severe stable COPD with controversial results. However, there is very little information on their use in acute exacerbations of COPD. The aim of this study is to find whether Leukotriene receptor antagonists may accelerate the lung function recovery & shorten the period of hospital stay when given in acute exacerbation of COPD. Patients & Methods: 54 patients were included in this study; their mean age was 59 years (SD +/− 7.50). The majority were males (72%). The trial was conducted at the Merjan teaching Hospital to assess the efficacy of oral montelukast on patients who were admitted to the hospital with acute exacerbation of COPD. The study group was randomly divided into group I (30 patients) which were given montelukast along with standard therapy throughout the hospital stay & group II (24 patients) which were given standard therapy alone. Improvements in lung function and duration of hospital stay were monitored. Results: There was better improvement in pulmonary function test results at discharge & on follow up 7 days post discharge & less duration of hospital stay in group I patients compared to group II. No serious adverse effects were noted during the course of the study. Conclusion: Our study suggests that there is a benefit of addition of oral montelukast over conventional treatment in the management of acute exacerbation of COPD